IMPROVING SPEAKING ABILITY IN ENGLISH THROUGH TOPIC-BASED-VLOG (TBV) - Pandu Prasodjo (Universitas Lambung Mangkurat, 2023)
As English becomes more relevant in today, speaking English in Indonesia needs to be improved to subsidize the change. Therefore, to improve Indonesian students English speaking performance, the usage of Topic Based Vlog is implemented. Therefore, the study aims to find the impact of the usage of TBV to improve the English-speaking performance for higher education student especially at UIB. The quantitative research method was implemented for this research. Then, to conduct research the Experimental method by having one group pre-test post-test was designed in the integrated speaking and listening class batch 2020. 20 English education students participated by producing a Vlog during the research. The TBV was based according to the lesson's schedule, for five weeks students have to make a vlog according to the topics based on the lesson's schedule. After conducting the vlog, the researcher manages the data by using paired sample T-test. The result of the t-test shows the sig. (2-tailed) equals 0.00 < 0.05, meaning that the result of the study shows TBV could significantly improve students’ English-speaking performance. The study finds that students particularly improve in vocabularies and grammar. And according to the interview TBV can also improve abilities beyond speaking such as confidence, student’s expressiveness, and many other. This study could become an outlook to the possibility of topic-based vlog as a means to improve the students speaking performance in UIB and other higher education institutions.Abstract: As English becomes more relevant in today, speaking English in Indonesia needs to be improved to subsidize the change. Therefore, to improve Indonesian students English speaking performance, the usage of Topic Based Vlog is implemented. Therefore, the study aims to find the impact of the usage of TBV to improve the English-speaking performance for higher education student especially at UIB. The quantitative research method was implemented for this research. Then, to conduct research the Experimental method by having one group pre-test post-test was designed in the integrated speaking and listening class batch 2020. 20 English education students participated by producing a Vlog during the research. The TBV was based according to the lesson's schedule, for five weeks students have to make a vlog according to the topics based on the lesson's schedule. After conducting the vlog, the researcher manages the data by using paired sample T-test. The result of the t-test shows the sig. (2-tailed) equals 0.00 < 0.05, meaning that the result of the study shows TBV could significantly improve students’ English-speaking performance. The study finds that students particularly improve in vocabularies and grammar. And according to the interview TBV can also improve abilities beyond speaking such as confidence, student’s expressiveness, and many other. This study could become an outlook to the possibility of topic-based vlog as a means to improve the students speaking performance in UIB and other higher education institutions.Keywords: Speaking English, speaking performance, improving Speaking, Vlog, Topic Based Vlog, Teaching Method